Association between urbanization and Internet addiction. Issue 3 (25th May 2022) - Ko, Chih-Hung; Yen, Ju-Yu; Lin, Pai-Cheng
Abstract : Purpose of review: Understanding the association between urbanization and Internet addiction is essential to the design and implementation of Internet addiction prevention measures in urban areas. This epidemiological review explores the urbanization-Internet addiction association and its potential underlying factors. Recent findings: Nine studies have reported that Internet addiction prevalence is higher in urban areas, but three studies have noted the opposite. Psychiatric disorders and stress are the most commonly mentioned factors underlying the association. The effects of urbanization on Internet availability, Internet cafes, online gaming, outdoor or interactive activities, and family regulation and monitoring have been suggested to lead to higher Internet addiction risk. The ongoing COVID-19 pandemic, obesity, sleep problems, and the migration of parents to urban areas in search of work have strengthened the effect of urbanization on Internet addiction. Summary: Early assessment and treatment provided by mental health services are crucial for mitigating the effect of urbanization on Internet addiction risk. Cities should be designed to provide adequate space for physical and interactive activities. To promote outdoor activities, air pollution, traffic congestion, and crime should be controlled. Prospective face-to-face studies involving analysis of data on pollution, traffic, and Internet addiction could provide evidence to elucidate the urbanization- Internet addiction association.